Hubungan Riwayat Pemberian Asi Eksklusif, Pola Asuh dan Pengetahuan Ibu Tentang Gizi dengan Terjadinya Stunting Pada Balita Usia 24-59 Bulan - Yuni Malinda Gusman; Lili Farlikhatun (Malahayati Nursing Journal, 2024)
ABSTRACT Stunting is a nutritional problem in society, especially toddlers. In 2021 there are 24.4% of children in Indonesia suffering from stunting. In 2022 there are 6.31 toddlers in the working area of the Karyamekar Health Center suffering from stunting. Many factors can lead to stunting, including a history of exclusive breastfeeding, parenting style and mother's knowledge of nutrition. This study aims to determine the relationship between history of exclusive breastfeeding, parenting style and mother's knowledge about nutrition with the occurrence of stunting in toddlers aged 24-59 months in the working area of the Karyamekar Health Center in 2023. The research design is a survey research with a cross sectional approach. The sample technique used is simple random sampling with a sample size of 280 people. Data analysis in this study was univariate and bivariate analysis using the SPSS program. From the univariate analysis, the results showed that 37 respondents (13.2%) had stunted toddlers, 189 respondents (67.5%) had babies who were not exclusively breastfed, 161 respondents (57.5%) had poor parenting and respondents who had low nutritional knowledge, namely 164 (58.6%). From the results of statistical tests with the chi square test, it was found that there was a relationship between history of exclusive breastfeeding (p value = 0.005), parenting values (pvalue = 0.000) and knowledge about nutrition (pvalue = 0.000) with the occurrence of stunting in toddlers aged 24-59 month. There is a relationship between a history of exclusive breastfeeding, parenting style and knowledge of nutrition with the occurrence of stunting in toddlers aged 24-59 months. It is hoped that health workers will provide interventions according to the problems that cause stunting. Keywords: Knowledge, Parenting, Exclusive Breastfeeding, Stunting  ABSTRAK Stunting merupakan salah satu masalah gizi dimasyarakat, terutama balita. Tahun 2021 terdapat 24,4 % anak di Indonesia menderita stunting. Tahun 2022 terdapat 6,31 balita diwilayah kerja puskesmas Karyamekar menderita stunting. Banyak faktor yang dapat menyebabkan terjadinya stunting antara lain riwayat pemberian ASI eksklusif, pola asuh dan pengetahuan ibu tentang gizi. Penelitian ini bertujuan untuk mengetahui hubungan riwayat pemberian ASI eksklusif, pola asuh dan pengetahuan ibu tentang gizi dengan terjadinya stunting pada balita usia 24-59 bulan di wilayah kerja puskesmas Karyamekar tahun 2023. Desain penelitian ini adalah penelitian survey dengan pendekatan cross sectional. Tekhnik sample yang digunakan adalah simple random sampling dengan jumlah sampel 280 orang. Analisa data dalam penelitian ini adalah analisa univariat dan bivariat dengan menggunakan program SPSS. Dari analisa univariat diperoleh hasil responden yang memiliki balita stunting yaitu 37 (13,2%), responden memiliki bayi tidak ASI Eksklusif yaitu 189 (67,5%), responden yang memiliki pola asuh kurang yaitu 161 (57,5%) dan responden yang memiliki pengetahuan gizi rendah yaitu 164 (58,6%). Dari hasil uji statistic dengan chi square test diperoleh bahwa terdapat hubungan antara riwayat pemberian ASI eksklusif (p value = 0,005), pola asuh nilai (pvalue = 0,000) dan pengetahuan tentang gizi (pvalue = 0,000) dengan terjadinya stunting pada balita usia 24-59 bulan. Terdapat hubungan antara riwayat pemberian ASI eksklusif, pola asuh dan pengetahuan tentang gizi dengan terjadinya stunting pada balita usia 24-59 bulan. Diharapkan bagi tenaga kesehatan untuk memberikan intervensi sesuai dengan masalah yang menyebabkan stunting. Kata Kunci: Pengetahuan, Pola Asuh, ASI Ekslusif, Stunting